FREQUENCY AND DIVERSITY OF POTENTIAL GENETIC MAKERS OF NUTRITION-RELATED DISEASES GENERATED FROM THE NEXT GENERATION SEQUENCING (NGS) PANEL - Rodriguez, Marietta; Zumaraga, Mark Pretzel; Perlas, Leah; Patalen, Chona; Duante, Charmaine; Nacis, Jacus; Concepcion, Mae Anne; Capanzana, Mario (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The ubiquity of lifestyle diseases is a challenge in the contemporary health of Filipinos that requires solid and practical answers. To lessen the impact of noncommunicable diseases (NCDs) on individuals and society, a comprehensive approach is needed, one that requires careful consideration of all the factors and risks associated with NCDs, as well as promote the interventions to prevent and control them. The study identified and profiled Single Nucleotide Polymorphisms (SNPs) associated with NCDs among adult Filipinos living in National Capital Region (NCR). The identification of SNPs will help in the assessment of likelihood of developing aforementioned diseases. METHODOLOGY Whole human blood samples from anonymized selected NCR participants were used for genomic deoxyribonucleic (DNA) extraction. Genomic DNA was isolated using the QIAamp DNA Blood Mini Kit. About 50 ng of anonymized DNA samples were sequenced using the Ion Torrent Proton (Life Technologies). Data were analyzed using the AmpliseqTM Variant Caller plug-in within the Ion Torrent Suite software (Invitrogen Life Technologies) and annotated using Ion Reporter software version 5.4. RESULTS The targeted sequencing of 502 published genes and SNPs associated with NCDs and other nutrition-related diseases was performed to a total of 1,160 samples. The identification of genes and SNPs underlying common noncommunicable diseases and other nutrition-related diseases performed in the Filipino population has tremendously helped determined level of susceptibility of the population towards development of debilitating but preventable diseases such as T2DM, obesity, cardiovascular diseases, osteoporosis and micronutrient deficiency. CONCLUSION AND RECOMMENDATION Genotyping of published SNP variants that interact with dietary composition to modulate biomarkers and health outcomes can provide a framework for the development of novel foods that are genotype dependent, in addition to the development of personalized dietary recommendations, aimed towards a more individualized/personalized strategy of health promotion, prevention and management of nutrition related diseases.